A sophisticated case of division of labour in the trimorphic stamens of the Cassia fistula (Leguminosae) flower. Issue 5 (27th August 2021) - Saab, Gabriella da Silva; Mansano, Vidal de Freitas; Nogueira, Anselmo; Maia, Isabele Carvalho; Bergamo, Pedro Joaquim; Paulino, Juliana Villela
Abstract: Buzz-pollinated pollen flowers have pollen as the primary resource for pollinators and must deal with a conflict between the exploitation of pollen grains by bees and pollination success. It has been hypothesized that heterostemony allows division of labour between stamens as a solution to the pollen dilemma. To test the division of labour hypothesis, we chose Cassia fistula, which has a trimorphic androecium and analysed androecium development, pollen grain release mechanisms and visitor behaviour. We explored the reflectance of floral organs and carried out an exclusion experiment to test the attractiveness of each stamen morph to the bee species. Finally, we explored the structural, ultrastructural and functional variation between the pollen grains, including pollen viability across stamen morphs. The differences among the three stamen morphs, which is developed from two whorls of the stamen, are the first evidence of the division of labour in our study system. Large Bombus and Xylocopa bees actively and exclusively exploited the pollen grains from the central poricidal anthers generating pollen deposition on their bodies. The reflectance pattern of floral organs indicated a targeting of these large bees to the central anthers, corroborated by the anther manipulative experiment where only the exclusion of the anthers positioned in the flower centre, especially the intermediate stamens, reduced bee visits. Both results revealed a division of labour, in which the intermediate stamen morph was responsible for both floral attractiveness and pollen resources. Only the largest stamen morph produced germinable pollen grains, highlighting their role as pollinating stamens. The smallest stamen morph has a less clear function, likely representing an economy in pollen production for feeding function. Our findings suggest that the evolution of the trimorphic androecium is associated with division of labour in large pollen flowers and can represent a strong strategy for circumventing the pollen dilemma, optimizing the feeding function by reducing pollen grain investment from central anthers. Abstract : Cassia fistula flowers offer only pollen as food to the pollinator. Because of its three sets of stamens, we investigated the division of labour. As the same pollen cannot fertilize the plant and feed the pollinator, the idea of a set of stamens producing pollen for fertilization and another producing pollen to feed, is a refined strategy to mitigate this dilemma. The central stamens (intermediate and smallest stamens) are more attractive, producing inviable pollen grains, the bees' choice for feeding. The largest stamens' viable pollen grains are deposited on the bees' back, confirming the division of labour in C. fistula flowers.